(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article analyses the evolution of literary translation practices in ancient and medieval Europe. It traces the development of translation from early examples, such as the translation of Homer’s “Odyssey” into Latin by Livius Andronicus, to the significant efforts in medieval Europe, including the translation of religious and secular texts. The study highlights key milestones, such as the translation of the Bible by John Wycliffe and Geoffrey Chaucer’s adaptation of Italian and French literary sources in his “Canterbury Tales”. The article also examines the role of translation in preserving and transmitting cultural and literary heritage, emphasizing its impact on the intellectual and spiritual life of European societies. By focusing on the historical practices and contributions of translators in these periods, the article sheds light on the foundations of literary translation as an essential tool for cultural exchange and intellectual development.